Investigating SARS-CoV-2 Neutralising Antibody Response in Sheep - Milena Samojlović; João R. Mesquita; Sérgio Santos-Silva; Malin Neptin; Joakim Esbjörnsson (Microorganisms)
SARS-CoV-2 can cause clinical and inapparent disease and mortality in several animals cohabitating with humans, and sheep are susceptible to SARS-CoV-2 due to virus–receptor interactions similar to those in humans. Hence, sheep have the potential to be infected, spread, and develop neutralising antibodies (NAbs) against SARS-CoV-2. The aim of this study was to investigate the prevalence of SARS-CoV-2 NAbs in farm animals after natural exposure to the virus. Serum samples were collected from sheep in the Serra da Estrela region in Portugal, both prior to and during the COVID-19 pandemic. The sera were tested by established SARS-CoV-2 pseudovirus systems for multiple SARS-CoV-2 variants (early—Wuhan, mid—Delta, Omicron—BA.1, and late—Omicron XBB, BQ.1.1). Partial neutralisation activity in Pre-pandemic and Mid-pandemic samples was observed, while no NAb activity was observed in Late-pandemic samples tested. Different levels of NAbs were observed between Pre-pandemic samples and those collected during the Mid-pandemic and Late-pandemic periods (p ≤ 0.01). Our results indicate that SARS-CoV-2 cross-species transmission may have occurred through human–sheep contacts on sheep farms during the pandemic, and that farm animals could contribute to the One Health Approach in zoonotic virus surveillance and pandemic preparedness.